Clinical pathology of intratracheal Mycoplasma mycoides subsp. capri infection in goats - KUMAR, HARENDRA; PARIHAR, N S; CHARAN, K; SINGH, K P (The Indian Journal of Animal Sciences, 2013)
Pleuropneumonia was produced by intratracheal inoculation of Mycoplasma mycoides subsp. capri in goats. The infection was characterized by pyrexia (105Â°-106oF; 41.3oC). watery to catarrhal nasal discharge, laboured respiration, moist respiratory rales, coughing and anorexia besides dullness, depression and emaciation. Haematological alterations revealed anaemic changes and significant leucopenia